Federal Service and the Constitution : The Development of the Public Employment Relationship - Rosenbloom, David H. (Book collections on Project MUSE., 2014)
Conceived during the turbulent period of the late 1960s when 'rights talk' was ubiquitous, Federal Service and the Constitution, a landmark study first published in 1971, strove to understand how the rights of federal civil servants had become so differentiated from those of ordinary citizens. Now in a new, second edition, this legal-historical analysis reviews and enlarges its look at the constitutional rights of federal employees from the nation's founding to the present. Thoroughly revised and updated, this highly readable history of the constitutional relationship between federal employees and the government describes how the changing political, administrative, and institutional concepts of what the federal service is or should be are related to the development of constitutional doctrines defining federal employees' constitutional rights. Developments in society since 1971 have dramatically changed the federal bureaucracy, protecting and expanding employment rights, while at the same time Supreme Court decisions are eroding the special legal status of federal employees. Looking at the current status of these constitutional rights, Rosenbloom concludes by suggesting that recent Supreme Court decisions may reflect a shift to a model based on private sector practices.--